List of IMF Member Countries with Delays in Completion of Article IV Consultations Mandatory Financial Stability Assessments Over 18 Months. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2016)
In accordance with Executive Board Decision No. 15106-(12/21), the Fund will publish on its external website a list of member countries whose Article IV consultations or mandatory financial stability assessments have been delayed by more than 18 months, as of the date of publication, since the expected deadline for conclusion. The latest version of this list, as shown in Appendix I, will be published on the Fund's external website on or after December 28, 2016.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Article IV Consultations Mandatory Financial; List Of IMF Member Country; List Of Member Country; PP; Website